2017
DOI: 10.3382/ps/pex061
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Escherichia coli infection in broiler chickens with Lactobacillus plantarum B1

Abstract: Two studies were performed to assess the efficacy of Lactobacillus plantarum B1 in prevention of pathogenic Escherichia coli K88 gastrointestinal infection in broilers. In an in vitro study, L. plantarum B1 showed resistance to acid and bile and inhibited the growth of E. coli K88. Additionally, L. plantarum B1 exhibited high ability to adhere to broiler embryo ileal epithelium. In an animal trial, 240 broilers at 1 d of age were randomly assigned to one of 4 treatment arms: negative control (NC) broilers fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
51
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 39 publications
9
51
0
2
Order By: Relevance
“…Notably, Dec et al [21] had reported that L. plantarum of domestic goose origin exhibited strong antagonism toward several poultry pathogens in vitro. Recently, Wang et al [22] reported both in vitro and in vivo antibacterial activities for L. plantarum of chicken origin. The ability of a bacterial strain to restrict the growth of pathogens has been proposed as one of the criteria for the selection of probiotics in many studies.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Dec et al [21] had reported that L. plantarum of domestic goose origin exhibited strong antagonism toward several poultry pathogens in vitro. Recently, Wang et al [22] reported both in vitro and in vivo antibacterial activities for L. plantarum of chicken origin. The ability of a bacterial strain to restrict the growth of pathogens has been proposed as one of the criteria for the selection of probiotics in many studies.…”
Section: Discussionmentioning
confidence: 99%
“…Using the selected strains of Lactobacillus as feed additives for poultry may result in similar effects with the effect of growth promoters of antibiotics, resulting in weight gain and better feeding efficiency, and resistance to pathogenic bacteria, such as Salmonella sp. [ 19 ], C. perfringens [ 20 , 21 ], E. coli [ 22 ], or Campylobacter sp. [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The anti-inflammatory effects of Lactobacillus spp. were largely reported in pathogen-infected broiler chickens (Cao et al, 2012 ; Wang et al, 2017 ). In the primary culture of chicken intestinal epithelial cells, we found that pre-incubation with L. acidophilus or L. fermentum decreased the C. perfringens -induced up-regulation of pro-inflammatory factors (IL-6, IL-8, iNOS, LITAF, IL-1β).…”
Section: Discussionmentioning
confidence: 99%